An Assessment of a Career Education Course in a Canadian School District - Stronck, David R.; Uhlemann, Max R. (Canadian Journal of Counselling and Psychotherapy, 2012)
Since 1978 the Greater Victoria School District has been offering a career education course for students in grades 10 and 12. In 1980 a sample of 154 of these students finishing the course in career education and a control group of 154 similar students without this course completed a 60-item questionnaire. Students completing the career education course demonstrated significantly greater satisfaction with their career needs being met and significantly reduced levels of needs in terms of their career development. The career education course seems successful in fulfilling some of the goals identified by the career counsellors. Achievement of other goals will require the cooperation of the entire staff in each school and of working people in the community.